Litigation in Cardiovascular Surgery: Risk Management Considerations in the Italian Context - Vittorio Bolcato; Giuseppe Speziale; Carlo Savini; Elisa Mikus; Giuseppe Basile; Livio Pietro Tronconi (Surgeries, 2024)
Background/Objectives: Malpractice in cardiovascular surgery was addressed from the forensic pathology perspective, offering reflections on risk prevention in the Italian context. Litigation and risk management in healthcare, following the Italian law on safety of care, clinical risk management and professional liability, should be viewed in an integrated manner. Methods: We conducted a narrative review on litigation data and the principal areas of complaint in Italy regarding the cardiovascular field. The aim is to discuss human, communicative, organisational, technological and regulatory factors that may play a role in this phenomenon. Results: We discuss the importance of information and consent and the management and monitoring of competences, particularly in specialised activities, given the current human capital deficit. Furthermore, we focus on the centrality of the surgical indication focusing on benefit-risk balance in light of clinical guidelines and team-based evaluation, such as by an emergency heart team, to better tailor care to patients. At the facility level, the minimum volume of activity and the requirements for human resources, specialisations, technologies and organisation standards needed for health activity authorisation are highlighted as foundational to risk prevention. Furthermore, we discussed the availability of the minimum diagnostic and care tools in compliance with guidelines and the role of company clinical and organisational protocols. Conclusions: In the surgical, time-sensitive, highly specialised and technologically advanced sector, the importance of enterprise risk prevention and broad, value-based governance to ensure healthcare quality and safety is emphasised.